Psycho-social dimensions of discriminatory widowhood rites and practices in South-Western Nigeria (2001)
Women, who find themselves single after marriage, whether through death of a husband or through divorce, learn that being the head of a household brings with it a set of special problems, the greatest being emotional. Even in a bad marriage, the survivor feels the loss. The concept of widowhood and widow's rites are examined as it is practised in South Western Nigeria. Apart from works already documented in the literature on psychosocial implications of widowhood practices, examples abound in our society which confirm the fact that there are indeed some discriminatory practices which have a lot of psychological and sociological implications on widows in South Western Nigeria. There is no doubt that these unhealthy attitudes do have some psychological and sociological implications on the individual in general. This paper, therefore, explains the various psychological and sociological implications, and offer recommendations on how the discriminatory practices against widows could be minimized and how their psychological and sociological effects would be reduced.